Pure Nautre Photography Company / Belcye Vivi Bolodin ... [et al.] - Bolodin, Belcye Vivi; Johnny, Meridith May; Awang Dinin, Noor Suhaiddah; Jimmy Akau, Phildelara; Simudah, Sarah Nadia; John, Yvette Priscilla (2013)
We are from Pure Nature Photography Company working on photography - oriented business and offer a complete photography services such as taking photos. There are a lot of Photography businesses out there, but what makes our photography business different from others is that we specialize in nature photography. We are in the tourism industry that specializes specifically in nature tourism where we are promoting it through our photography shooting. Meaning to say, we are taking customer's photo with nature as their background. Our photo shoot is unique because on the same time customer is joining our business they are also promoting nature tourism and helping nature. We are a company that provides photography service to the public at a reasonable price depending on the size of the photo, number of people and the location of the photo shoot. Outdoor photo shoot specifically around Sabah which is also known as the land below the wind. The location of our business is at Unite B-0-1, Second Floor, Karamunsing Capital, Jalan Nanas, 88100 Kota Kinabalu, Sabah which situated at the heart of the Kota Kinabalu city centre. It also surrounded by commercial complexes, government offices and established neighbourhoods such as Kompleks Karamunsing, Beverly Hotel, Kompleks Kuwasa (KWSP), Wisma SESB and many more. Business plan is prepared for each of the partners of the company, prospects for future customers and targeted market also future investors who might be interested of investing in the company. Owners and partners of the company consist of Meridith May Johnny, Sarah Nadia bte Simudah, Phildelara Jimmy Akau, Belcye Vivi Bolodin, Yvette Priscilla John and Noor Suhaiddah binti Awang Dinin. Everybody that has the ability to pay our services which are in needs of photography services based on each packages that the company had provided. We aim to promote nature tourism since nowadays everybody is going green and becoming more aware towards the environment so there is definitely a demand for it.